Phenotypic Screening of Bread Wheat (Triticum spp L.) Germplasm Collection for Yellow and Leaf Rust Disease Resistance - Demeke Zewdu; Tafesse Solomon; Gadisa Alemu; Alemu Dabi; Negash Geleta; Berhanu Sime; Rut Duga; Abebe Delesa; Habteamriam Zegeye; Abebe Getamesay; Bayisa Asefa; Dawit Asnake; et al. (International Journal of Economic Plants)
The Research was conducted at KARC during June to November, 2023 to phenotypic screening of bread wheat genotypes for yellow and leaf rust resistance.  Both rusts were recorded based on the modified Cobb scale. Severity of yellow rust showed from immune to 70%. 826 genotypes showed slow rusting resistance ranging from 0–30%), 575 genotypes observed as slow rusting plant resistance ranging from 31–50%) and 96 genotypes observed as low adult plant resistance (>50% of yellow rust severity). Tested genotypes showed diverse reactions for yellow rust ranging from immune to susceptible responses. 57 genotypes were observed immune, 161 genotypes were showed moderately resistant reaction type. 317 genotypes were observed moderately susceptible reaction and 962 genotypes were observed susceptible reactions for yellow rust response. The leaf rust severity of the studied genotypes showed from immune  to 90. 607 genotypes (showed slow rusting resistance ranging from 0–20% of severity), 563 genotypes observed as slow rusting plant resistance ranging from 21–50% of severity) and 326 genotypes observed as low adult plant resistance (>50% of leaf rust severity. Tested genotypes showed diverse reactions for leaf rust ranging from immune to susceptible responses. 58 genotypes were observed immune, 30 genotypes were observed moderately resistant, 80 genotypes were observed moderately resistant to moderately susceptible, 464 genotypes were showed moderately susceptible reaction, 864 genotypes were showed susceptible reactions for leaf rust disease response. Based on yellow rust, leaf rust and agronomic performance 76 genotypes were selected for the next breeding step.